2017
DOI: 10.12659/msm.904227
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Contrast-Enhanced Ultrasonography for Predicting Esophageal Varices in Patients with Hepatitis B Virus (HBV)-Related Cirrhosis

Abstract: BackgroundThe aim of this study was to investigate the usefulness of contrast-enhanced ultrasonography (CEUS) in predicting of esophageal varices (EV) and assessing high-risk EV in patients with hepatitis B virus (HBV)-related cirrhosis.Material/MethodsPatients with HBV-related cirrhosis who had undergone endoscopy were prospectively recruited. Hepatic dynamic CEUS was performed. Regions of interest (ROI) were drawn on the hepatic artery, hepatic vein, portal vein, and liver parenchyma to measure the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…Over the years, CEUS has also been used to investigate the presence of oesophageal varices (EV) based on time–intensity curves [ 31 , 32 ], and the results show that CEUS can predict EV. CEUS has also been used in animal models to investigate liver fibrosis [ 33 , 34 ], and it was concluded that this method has diagnostic performance for liver fibrosis, similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, CEUS has also been used to investigate the presence of oesophageal varices (EV) based on time–intensity curves [ 31 , 32 ], and the results show that CEUS can predict EV. CEUS has also been used in animal models to investigate liver fibrosis [ 33 , 34 ], and it was concluded that this method has diagnostic performance for liver fibrosis, similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol, drugs, and toxic chemical substances may even cause liver cancer. 38 In recent years, the exploration of functional foods that may contribute to alleviating this problem in people with liver disease has attracted considerable attention. In the current research, we observed that salecan supplementation reduced the liver weight to body weight ratio in mice with CCl 4 -induced liver injury, suggesting that salecan treatment could be an approach for maintaining optimal hepatic function.…”
Section: Discussionmentioning
confidence: 99%
“…The recently developed contrast-enhanced ultrasound (CEUS) perfusion imaging has markedly expanded the possibilities for detailed hepatic hemodynamics [4]. It has been demonstrated that CEUS-based analysis of the transit time between the hepatic vein (HV) and hepatic artery (HA) or portal vein (PV), can be useful for predicting the grade of PH [5,6,7,8].…”
Section: Zusammenfassungmentioning
confidence: 99%